Laminar mixing in a SMX static mixer evaluated by positron emission particle tracking (PEPT) and magnetic resonance imaging (MRI). (1st December 2015) - Mihailova, Olga; Lim, Victor; McCarthy, Michael J.; McCarthy, Kathryn L.; Bakalis, Serafim
Abstract: Static mixers are implemented across many industries and are used for mixing, heating and reacting processes. This paper reports the combined use of positron emission particle tracking (PEPT) and magnetic resonance imaging (MRI) to assess mixing in the industrially important SMX static mixer geometry. The focus of this study was distributive mixing for a Newtonian fluid, glycerol, flowing in the laminar regime in the standard SMX static mixer. By implementing PEPT and MRI techniques, the work elucidated mixing indices that incorporate both local velocities and concentration fields within the structure of the mixer element at 0.5 mm intervals over a length of nine 1.0 L / D SMX elements. The experimental results are placed in context with previously published computational studies for this geometry. Highlights: Two experimental techniques are combined for quantitative measure of mixedness. Mixing is more effective in the initial elements of the SMX than predicted from CFD. Combination of MRI and PEPT techniques opens a range of complementary studies.